2020
DOI: 10.1186/s12903-020-1054-4
|View full text |Cite|
|
Sign up to set email alerts
|

Acute and chronic diabetes complications associated with self-reported oral health: a retrospective cohort study

Abstract: Background Oral health is associated with diabetes, but the chances of experiencing acute or chronic diabetes complications as per this association is unknown in Canada’s most populous province, Ontario. This study assesses the impact of self-reported oral health on the likelihood of experiencing acute and chronic complications among a cohort of previously diagnosed diabetics. Methods A retrospective cohort study was conducted of diabetics (n = 5183) who participated in the Canadian Community Health Survey 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
(73 reference statements)
0
7
2
Order By: Relevance
“…A large proportion of respondents rated their oral health status as poor to fair (45.8%), and this was higher than the Australian general population (24%) [ 25 ], which is understandable since diabetes predisposes people to various oral health problems [ 3 ]. This finding was also higher than those reported in Canada (21%) which has a similar healthcare system [ 26 ]. A possible reason for this variation could be the presence or absence of diabetes related chronic or acute complications in the respondents, as complications have been found to be associated with greater frequency of reporting poor oral health status [ 26 ].…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…A large proportion of respondents rated their oral health status as poor to fair (45.8%), and this was higher than the Australian general population (24%) [ 25 ], which is understandable since diabetes predisposes people to various oral health problems [ 3 ]. This finding was also higher than those reported in Canada (21%) which has a similar healthcare system [ 26 ]. A possible reason for this variation could be the presence or absence of diabetes related chronic or acute complications in the respondents, as complications have been found to be associated with greater frequency of reporting poor oral health status [ 26 ].…”
Section: Discussioncontrasting
confidence: 67%
“…This finding was also higher than those reported in Canada (21%) which has a similar healthcare system [ 26 ]. A possible reason for this variation could be the presence or absence of diabetes related chronic or acute complications in the respondents, as complications have been found to be associated with greater frequency of reporting poor oral health status [ 26 ]. In our study, half of the respondents reported to have other chronic diseases in additional to diabetes and the majority had a lower socio-economic status, so these factors would have played an additional role in the higher prevalence of poor oral health status.…”
Section: Discussioncontrasting
confidence: 67%
“…Since all Ontario residents are covered through a single-payer insurance system for physician, hospital-based care and home care services, and drugs for residents 65 years of age and older, healthcare encounters can be linked across systems through individual health card numbers and each resident receiving a unique ICES Key Number (IKN). 15 Reference standard database CorHealth Ontario's cardiac registry was selected as the reference standard. 16,17 The CorHealth cardiac registry captures select clinical data on all cardiac procedures performed in Ontario catheterization laboratories.…”
Section: Health Administrative Data Sourcesmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in the Competing interests section: “Carlos Quiñonez receives consulting income for dental care related issues from Green Shield Canada” should be added.…”
Section: Correction To Bmc Oral Health (2020) 20:66 Https:/mentioning
confidence: 99%